2017
DOI: 10.1007/s10552-017-0955-2
|View full text |Cite
|
Sign up to set email alerts
|

Kaiso is highly expressed in TNBC tissues of women of African ancestry compared to Caucasian women

Abstract: PurposeTriple-negative breast cancer (TNBC) is most prevalent in young women of African ancestry (WAA) compared to women of other ethnicities. Recent studies found a correlation between high expression of the transcription factor Kaiso, TNBC aggressiveness, and ethnicity. However, little is known about Kaiso expression and localization patterns in TNBC tissues of WAA. Herein, we analyze Kaiso expression patterns in TNBC tissues of African (Nigerian), Caribbean (Barbados), African American (AA), and Caucasian A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 48 publications
(66 reference statements)
0
25
2
Order By: Relevance
“…[156][157][158][159][160]162 Most of these findings are more evident for young, HRpatients. 155,158,161 Other features, such as a differential mutational landscape 157,163 and higher frequency of DNA copy number alterations, 161 have been reported for AA/Bs compared with NHWs, in addition to the existence of differential immune and inflammatory pathways involved in tumour-specific immune responses between the two groups. 164,165 As stated above, obesity is associated with increased circulating levels of insulin and inflammatory cytokines, such as IL-6, IL-8 and TNF-α and CD8 + T cells and M1 macrophages, which contribute to the development of a pro-tumorigenic microenvironment and more aggressive tumour characteristics, leading to TNBC biology in AA/B women.…”
Section: Tumour Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…[156][157][158][159][160]162 Most of these findings are more evident for young, HRpatients. 155,158,161 Other features, such as a differential mutational landscape 157,163 and higher frequency of DNA copy number alterations, 161 have been reported for AA/Bs compared with NHWs, in addition to the existence of differential immune and inflammatory pathways involved in tumour-specific immune responses between the two groups. 164,165 As stated above, obesity is associated with increased circulating levels of insulin and inflammatory cytokines, such as IL-6, IL-8 and TNF-α and CD8 + T cells and M1 macrophages, which contribute to the development of a pro-tumorigenic microenvironment and more aggressive tumour characteristics, leading to TNBC biology in AA/B women.…”
Section: Tumour Biologymentioning
confidence: 99%
“…Differences in tumour biology according to race/ethnicity have also been described. Studies have found differences in gene expression [155][156][157] and methylation patterns [158][159][160][161] between AA/Bs and NHWs, which might have a potential impact on patient outcomes. [156][157][158][159][160]162 Most of these findings are more evident for young, HRpatients.…”
Section: Tumour Biologymentioning
confidence: 99%
“…As a first step in testing this hypothesis, the Daniel and Yates labs independently examined a cohort of breast cancer patients and observed that nuclear Kaiso is significantly overexpressed in breast tumor tissues of patients with an African ancestry [13, 99]. Jones et al further observed that nuclear Kaiso was overexpressed in primary tumor and paired lymph node metastases of AA women compared to Caucasian women (CaW) [13], and AA women with nuclear Kaiso had a decreased overall survival compared to CaW with nuclear Kaiso expression.…”
Section: Kaiso and Racial Disparities In Cancermentioning
confidence: 99%
“…These patient cohorts were selected based on the premise that they represent more homogeneous populations of African ancestry than African Americans. Bassey-Archibong et al found that Nigerian and Barbadian women were diagnosed with TNBC at much younger ages than AA and CauW [99], and that nuclear Kaiso levels were significantly higher in Nigerian, Barbadian and AA women compared with CauW. The high levels of nuclear Kaiso expression in women of African Ancestry compared to their Caucasian counterparts, suggests a role for Kaiso in TNBC racial disparity, and forms the premise for ongoing studies in the Daniel lab to further decipher this phenomenon.…”
Section: Kaiso and Racial Disparities In Cancermentioning
confidence: 99%
“…Limited therapeutic options are available for TNBC patients and consequently can result in aggressive metastatic disease, with greater mortality rates in African American (AA) women, relative to Caucasian-American (33,34). This health disparity may arise due to diagnosis at later stages of the disease (35) or a predisposed racially distinct genetic or epigenetic profile (36,37) with a propensity toward an overactive oncogenic p38 MAPK, Wnt/β-catenin, IGF2/ERbeta signaling axis (38)(39)(40). Additional factors to a health disparity arising in AA women regarding TNBC include vitamin D deficiencies (41) socioeconomic factors, later stage diagnosis, obesity, or even breast feeding patterns (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%